2009
DOI: 10.1007/s00167-009-0860-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of injury mechanisms and related factors in ACL-injured female carving skiers

Abstract: While ACL injury mechanisms in skiers using traditional skis are well studied, no study has yet investigated the distribution of injury mechanisms in carving skiers. In traditional skiers, the backward twisting fall seems to be the dominant injury mechanism, especially in female skiers. Female recreational skiers have a threefold higher risk to sustain an ACL injury than male skiers; therefore, it is important to determine if carving skis influence the distribution of injury mechanisms and the related frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
2
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 30 publications
9
35
2
5
Order By: Relevance
“…In accordance with other studies, the most common type of self-reported fall among knee injured skiers seems forward falling with body rotation (‘valgus external rotation’) 14 18 19. The larger amount of reported binding release among forward falls with and without body rotation becomes plausible because current bindings are mostly designed to release during a simple forward fall (upward release function of the heel piece) or during a forward fall with body rotation (side release function of the toe piece of the ski binding) 20.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with other studies, the most common type of self-reported fall among knee injured skiers seems forward falling with body rotation (‘valgus external rotation’) 14 18 19. The larger amount of reported binding release among forward falls with and without body rotation becomes plausible because current bindings are mostly designed to release during a simple forward fall (upward release function of the heel piece) or during a forward fall with body rotation (side release function of the toe piece of the ski binding) 20.…”
Section: Discussionsupporting
confidence: 90%
“…These findings align with earlier studies [5][6][7][8]. Since the introduction of the carving ski in 1993, female skiers have dominated knee injury trends.…”
Section: Discussionsupporting
confidence: 91%
“…When injury does happen, there is a 50% chance it is to the lower extremity, which today usually means an ACL injury [14,15]. Most of the ACL injuries among recreational skiers are reported to occur during falling [16,17]. The three mechanisms of ACL injury all involve falling either in a backward or a forward direction.…”
Section: What Does It Mean For Safety?mentioning
confidence: 99%